INTERRELATIONSHIPS BETWEEN NON-FAMILY BUSINESS MEMBERS, NEPOTISM AND PRIDE IN FAMILY BUSINESS SUCCESSION - Maharani, Anita; Yokung, Laurencia Bernadette; Ignasius, Ervan; Suwargo, Nixon (Directorate of Academic Research and Community Services, 2020)
The purpose of this study is to raise issues related to the succession of family-owned businesses, influenced by the involvement of members outside the family business and have something to do with nepotism and self-esteem. Conceptually, there is a relationship between members outside the family business, nepotism, and self-esteem in the family business. When there is professional involvement, the effect is positive on the family business's succession. When there is a practice of nepotism, this will harm the family business. And finally, regarding self-esteem, which will have a positive influence on the family business. This research's approach is quantitative, by looking at how much impact the independent variable has on the dependent where the sample of this study is 128 respondents. The results of this study indicate that professional existence does not affect the success of the family business. Simultaneously, nepotism will harm the family business, and then self-esteem will affect the family business's succession.